Religious Moderation in the Perspective of Muslim Philosopher: Theory and Practice - Humaidi Humaidi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
One of the teachings and the difference between philosophy and other sciences is the importance of rational and objective thinking. The implication of this teaching is the birth of an open-minded, inclusive view and acceptance o the truth from wherever it comes, including from different religions and cultures. Openness and acceptance of differences are the indicators of religious moderation. Therefore, there is an inherent relationship between openness and religious moderation. Without an inclusive view, there is no religious moderation. Likewise, a person's inclusive and moderate view will be present only if he thinks rationally and objectively. This article aims to analyze the meaning of religious moderation from the perspective of Muslim philosophers and its implementation in history, either in the global or Indonesian context. This research answers and seeks an alternate solution to the problem of extremism and radicalism in the name of religion. The method used is philosophical and historical-hermeneutic. In addition to library data, the research sources also use field data obtained through observation and interviews with students, alumni, and lecturers of Aqidah and Islamic Philosophy (AFI) in Indonesia.